2012
DOI: 10.3402/tellusb.v64i0.18738
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the ocean carbon cycle in response to the North Atlantic Oscillation

Abstract: A B S T R A C T Climate modes such as the North Atlantic Oscillation (NAO), representing internal variability of the climate system, influence the ocean carbon cycle and may mask trends in the sink of anthropogenic carbon. Here, utilising control runs of six fully coupled Earth System Models, the response of the ocean carbon cycle to the NAO is quantified. The dominating response, a seesaw pattern between the subtropical gyre and the subpolar Northern Atlantic, is instantaneous ( B3 months) and dynamically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 92 publications
(123 reference statements)
5
34
0
1
Order By: Relevance
“…We find clear indications of ENSO in the SD patterns of SST, DIC and pCO 2 , and a weak signal for pH. Another area of high natural variability is the North Atlantic, which is influenced by modes like the North Atlantic Oscillation (NAO; Hurrell and Deser, 2009) or changes in the Atlantic Meridional Overturning Circulation (AMOC; Carton and Häkkinen, 2011), both known for affecting the ocean carbon cycle (e.g., Keller et al, 2012;Perez et al, 2013). A further region with high variability in the ocean carbon system is the Southern Ocean (see e.g., Bacastow, 1976;Marinov et al, 2006;Lovenduski et al, 2007;Le Quéré et al, 2007;Resplandy et al, 2013b), where we find a corresponding signal in the ensemble SD pCO 2 pattern.…”
Section: Toe -Ensemble Meanmentioning
confidence: 95%
See 2 more Smart Citations
“…We find clear indications of ENSO in the SD patterns of SST, DIC and pCO 2 , and a weak signal for pH. Another area of high natural variability is the North Atlantic, which is influenced by modes like the North Atlantic Oscillation (NAO; Hurrell and Deser, 2009) or changes in the Atlantic Meridional Overturning Circulation (AMOC; Carton and Häkkinen, 2011), both known for affecting the ocean carbon cycle (e.g., Keller et al, 2012;Perez et al, 2013). A further region with high variability in the ocean carbon system is the Southern Ocean (see e.g., Bacastow, 1976;Marinov et al, 2006;Lovenduski et al, 2007;Le Quéré et al, 2007;Resplandy et al, 2013b), where we find a corresponding signal in the ensemble SD pCO 2 pattern.…”
Section: Toe -Ensemble Meanmentioning
confidence: 95%
“…Possible reasons for the model spread in the Southern Ocean include the inadequate representation of bottom-water formation processes in many CMIP5 models (Heuzé et al, 2013) and a systematic wind bias inherent to many models, which impacts physical processes like Antarctic Circumpolar Current and Southern Ocean water mass formation and, consequently, the ocean carbon cycle (Swart and Fyfe, 2012). In areas with high natural variability, such as the equatorial Pacific or the North Atlantic, IMS might arise from differences in time and space of the representation of climate modes such as ENSO or NAO (e.g., Keller et al, 2012). Another possible factor is the model resolution, especially in areas dominated by local processes such as coastal upwelling.…”
Section: Toe -Ensemble Meanmentioning
confidence: 99%
See 1 more Smart Citation
“…These variations are at least partially attributed to oceanic variability in the North Atlantic associated with a surface pressure pattern change known as North Atlantic Oscillation (Wetzel et al, 2005;Thomas et al, 2008;Tjiputra et al, 2012). In a model study with six coupled Earth system models, Keller et al (2012) identified a see-saw pattern of variations in sea surface pCO 2 between the North Atlantic subtropical gyre and the subpolar Northern Atlantic with an amplitude of ±8 ppm. Such variations make identification of long-term trends in oceanic carbon uptake more difficult.…”
Section: Detection Of Ongoing Ocean Carbon Sink Strength Variabilitymentioning
confidence: 99%
“…Une reconstruction des projections atmosphériques futures, combinant les projections d'occurrence des régimes aux caractéristiques observées, peut également être envisagée pour forcer un modèle d'océan (de plus haute résolution horizontale que la composante océanique des modèles de climat, par exemple), afin de s'affranchir de l'effet négatif des biais moyens de l'atmosphère dans les modèles de climat. Au-delà de ces problématiques, l'approche en régi-mes de temps semble aussi prometteuse pour mieux comprendre l'influence de la variabilité atmosphérique sur la biogéo-chimie marine, et plus particulièrement sur les concentrations en carbone (Keller et al, 2012) et en chlorophylle (Patara et al, 2011) dans l'océan.…”
Section: Bilan Et Perspectivesunclassified